Cystic partially differentiated nephroblastoma-like lesion following neo-adjuvant chemotherapy for nephroblastoma: A case report and review of the literature - C. Bruce-Brand; M. Reyes-Múgica; A. van Zyl; P.T. Schubert (Elsevier, 2020)
Cystic partially differentiated nephroblastoma (CPDN) and cystic nephroblastoma are paediatric renal tumours characterised by the presence of a variable combination of primitive epithelium, immature stroma and blastema. Cystic nephroblastoma can be identified by the presence of solid expansile areas of tumour which are absent in CPDN. The distinction can pose diagnostic difficulty pre-operatively and is of paramount importance as their metastatic potential, prognosis and hence therapeutic strategies differ.We present a 2 year old girl, with two right renal masses, diagnosed pre-operatively as synchronous nephroblastoma based on clinical, radiological and cytologic findings. Neo-adjuvant chemotherapy was administered followed by nephrectomy. Two discrete tumours were present, one being an epithelial predominant nephroblastoma and the other a CPDN. The CPDN showed an unusual spectrum of epithelial cells lining the cysts including intestinal type epithelium with goblet cells.This case represents one of three cases described thus far in the literature of concomitant nephroblastoma and CPDN or cystic nephroma (CN) and is the only case in which nephroblastoma occurred synchronously with CPDN. Due to neo-adjuvant therapy being instituted for the nephroblastoma, this case provides unique insights into possible chemotherapy induced changes in a CPDN (usually treated by surgical excision alone).This case highlights several important issues in paediatric cystic renal neoplasms, particularly the distinction between cystic nephroma, CPDN and cystic nephroblastoma. The differential diagnosis of cystic paediatric renal neoplasms is broad and requires appropriate clinical, radiological and histological assessment, often with ancillary immunohistochemical and molecular studies to arrive at a correct diagnosis. Histologic features of chemotherapy effect, although well-described in nephroblastoma, are not well-described in CPDN. Based on our knowledge of possible chemotherapy induced changes in nephroblastoma, such as maturation of epithelial and stromal elements that may be so marked as to mimic mature teratoma, we hypothesize that this case demonstrates such changes within a CPDN.